Deciphering the spectrum of astrocyte diversity: Insights into molecular, morphological, and functional dimensions in health and neurodegenerative diseases - Fumito Endo (Neuroscience Research)
Astrocytes are the most abundant and morphologically complex glial cells that play active roles in the central nervous system (CNS). Recent research has identified shared and region-specific astrocytic genes and functions, elucidated the cellular origins of their regional diversity, and uncovered the molecular networks for astrocyte morphology, which are essential for their functional complexity. Reactive astrocytes exhibit a wide range of functional diversity in a context-specific manner in CNS disorders. This review discusses recent advances in understanding the molecular and morphological diversity of astrocytes in healthy individuals and those with neurodegenerative diseases, such as Alzheimer’s disease, Huntington’s disease, and amyotrophic lateral sclerosis.